Genetic characterization of the Central Javanese duck using microsatellite markers - R, Susanti; Ari, Yuniastuti; Agustin, Dian Kartikasari (Penerbit Universiti Kebangsaan Malaysia, 2021)
Duck conservation strategy based on genetic characteristics has been undertaken to preserve indigenous breeds and produce high quality offspring. In addition, the genetic characteristic analysis provides further information for studying avian influenza viruses. The aim of this research was to study the genetic characterisation of indigenous Central Javanese duck in Indonesia using microsatellite markers. Microsatellite or simple sequence repeats (SSR) or short tandem repeats (STR) of various breeds of Central Javanese duck were analysed on 35 local ducks which consisted of seven variants of Javanese ducks in Central Java. Ten pairs of duck microsatellite primers were used to amplify the DNA from feathers. Nine out of 10 microsatellite loci (90%) demonstrated polymorphic patterns containing 50 alleles. The number of alelles varied from two to 10 alleles at various polymorphic microsatellite loci with an average of 5.56 alelles per locus. From the study, CAUD013 locus was determined as the highest heterozygosity with 0.882 score while CAUD030 locus was the lowest one with 0.034 score. Similarly, CAUD030 locus had the lowest PIC score (0.30) whereas the CAUD013 locus had the highest PIC value (0.869). Hence, it was showed that microsatellite markers were highly polymorphic in several loci for the Central Javanese duck and may be useful for genetic description of other native duck in terms of species conservation.